THE MAIN DIRECTIONS OF POVERTY REDUCTION IN OUR COUNTRY - Musinov Dilshod Sultanovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the nature of poverty and the population of the Republic of Uzbekistan in poverty, their problems, specific recommendations for the reduction and elimination of poverty, scientific recommendations.